Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen di Indomaret Tawangsari Sukoharjo - Jumiyati, Jumiyati; Hendratmoko, Christiawan (Graduasi: Jurnal Bisnis & Ekonomi, 2014)
This study was carried out on Indomaret Minimarket in Tawangsari, Sukoharjo. The goal of the study are: (1) To know the influence of service quality (tangible, reliability, responsiveness, assurance, and empathy) toward consumersâ satisfaction in Indomaret Minimarket. (2) To know the dominant factor of service quality (tangible, reliability, responsiveness, assurance, and empathy) that influence toward consumersâ satisfaction in Indomaret Minimarket. The hypothesis drawnare: (1) Presummed that there are influence of service quality (tangible, reliability, responsiveness, assurance, and empathy) toward consumersâ satisfaction in Indomaret Minimarket. (2) Presummed that tangible has dominant influence toward consumersâ satisfaction in Indomaret Minimarket. The sample of this study is 100 consumers that shopped in Indomaret Minimarket, with primary data. Technique of Analysis applied are validity test, reliability test, multiple linear regression, t-test , F- test and coefficient of determination. The results of this study are: (1) There are simultaneous and significant influence of service quality (tangible, reliability, responsiveness, assurance, and empathy) toward consumersâ satisfaction in Indomaret Minimarket. (2) Tangibles has dominant influence toward consumersâ satisfaction in Indomaret Minimarket in Tawangsari, Sukoharjo